Multilayer Multipurpose Caches for OpenMP Target Regions on FPGAs [Data set] - Brandner, Julian; Mayer, Florian; Philippsen, Michael (2024)
This archive contains the benchmarks used in the conference paper "Multilayer Multipurpose Caches for OpenMP Target Regions on FPGAs" <br
Keywords: FPGA; OpenMP; target offloading; hardware cache